Ultrasound-Guided Thrombin Injection Is a Safe and Effective Treatment for Femoral Artery Pseudoaneurysm in the Morbidly Obese. (August 2017) - Yoo, Taehwan; Starr, Jean E.; Go, Michael R.; Vaccaro, Patrick S.; Satiani, Bhagwan; Haurani, Mounir J.
Introduction: Ultrasound-guided thrombin injection (UGTI) is a well-established practice for the treatment of femoral artery pseudoaneurysm. This procedure is highly successful but dependent on appropriate pseudoaneurysm anatomy and adequate ultrasound visualization. Morbid obesity can present a significant technical challenge due to increased groin adiposity, resulting in poor visualization of critical structures needed to safely perform the procedure. We aim to evaluate the safety and efficacy of UGTI to treat femoral artery pseudoaneurysm in the morbidly obese. Methods: This is a retrospective cohort study in which all patients who underwent UGTI at The Ohio State University Ross Heart Hospital from 2009 to 2014 were analyzed for patient characteristics and stratified by body mass index (BMI). Patients with BMI ≥ 35 were considered morbidly obese and were compared to patients with a BMI < 35. Outcome was failed treatment resulting in residual pseudoaneurysm. Results: Our cohort consisted of 54 patients who underwent thrombin injection. There were 41 nonmorbidly obese and 13 morbidly obese patients. Mean age was 64.5 years. The cohort was 44.4% male. There were 6 failures, of which 1 underwent successful repeat injection and 5 underwent open surgical repair. There was no statistically significant difference in failure between nonmorbidly obese and morbidly obese patients (9.8% vs 15.4%, P = .45). There were no embolic/thrombotic complications. Conclusion: Ultrasound-guided thrombin injection is a safe and effective therapy in the morbidly obese for the treatment of femoral artery pseudoaneurysm. In the hands of experienced sonographers and surgeons with adequate visualization of the pseudoaneurysm sac, UGTI should remain a standard therapy in the morbidly obese.